The Quality of Operational Performance of STIE Indonesia Banking School Student Organization with Remotely Operationally (Study on STIE Indonesia Banking School Student Organization in the 2020/2021 Period) - Mohamad Ramadhan Argakoesoemah; Rifqi Alif Nugraha; Dhea Ananda Christinadhi; Donna ylvia (Journal of Computer Science Advancements, 2023)
This study is focused on identifying the influence of communication, organizational culture and work-from-home on performance to study in student organizations of STIE Indonesia Banking School in the 2020/2021 period. The questionnaire was distributed to 99 respondents and data were analyzed through SmartPLS version 3.3.3. The results of this study indicate that 1) There is a positive influence between Communication and Performance; 2) There is a positive influence between Organizational Culture and Performance; 3) There is no influence between Work from Home and Performance; 4) There is a positive influence between Organizational Culture and Communication; 5) There is a positive influence between Work from Home and Organizational Culture.